2018
DOI: 10.1155/2018/1896057
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characteristics and Microbiological Quality of Honey Produced in Benin

Abstract: Honey is a very complex biological product. It has great diversity, giving it a multitude of properties, both nutritionally and therapeutically. This study aimed to study the physicochemical and microbiological characteristics of honeys collected during the dry and rainy seasons in the different phytogeographical areas of Benin. The study revealed that all honeys had pH, water content, electrical conductivity, ash content, free acidity, total sugars, and reducing sugars, respectively, ranging within 3.65-4.09;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
33
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 33 publications
9
33
2
1
Order By: Relevance
“…The results of the proximate analysis showed that the parameters tested in the honey samples conformed with the standards of EU and Codex recommendations for honey produced from nectariferous plants [21,22] (Table 2). These findings are also comparable to the works of previous authors not only in Nigeria [12,1,34,15], but some other parts of the world [35,3]. The variations observed in the values of the moisture, crude protein, ash, pH and free acidity contents of the honeys sourced from different locations of the study area may be attributed to the differences in microclimate and soil properties on which the vegetation of the of the areas depend on for sustenance [36].…”
Section: Physicochemical Analysissupporting
confidence: 90%
See 1 more Smart Citation
“…The results of the proximate analysis showed that the parameters tested in the honey samples conformed with the standards of EU and Codex recommendations for honey produced from nectariferous plants [21,22] (Table 2). These findings are also comparable to the works of previous authors not only in Nigeria [12,1,34,15], but some other parts of the world [35,3]. The variations observed in the values of the moisture, crude protein, ash, pH and free acidity contents of the honeys sourced from different locations of the study area may be attributed to the differences in microclimate and soil properties on which the vegetation of the of the areas depend on for sustenance [36].…”
Section: Physicochemical Analysissupporting
confidence: 90%
“…The low moisture content, the acidic and free acidity levels of the samples indicate that the honeys have potential for long shelf life and strong inhibitory property against microbial activity. The acidity in honey is attributed to the presence of organic acids such as gluconic acid and inorganic ions [35]. The considerably low free acidity especially in samples from Ezinifite II and Nnokwa is a good indication of good quality honey because high acidity has been reported to facilitate the breakdown of hexoses to hydroxymethyl furfural [37], therefore the level of acidity recorded is an indication of freshness of the honeys.…”
Section: Physicochemical Analysismentioning
confidence: 99%
“…As shown in the Table 6, aerobic mesophilic bacteria were present in all honey samples, except in sample H1 (Bouyablane) and ranged from (0 to 45 CFU/g), which is in accordance with the French standards (levels of aerobic mesophilic bacteria below 1000 CFU/g) [49]. ese results are generally lower than that obtained in Moroccan monofloral honeys of ymus broussonetti, and Euphorbia resinifera [25].…”
Section: Microbiological Qualitysupporting
confidence: 75%
“…More importantly, honey possess antibacterial properties 2 . It is also use in the treatment of cardiovascular diseases, cancers, cataract and several inflammatory diseases, as well as, wound healing 3 . The criteria for the quality of honey were specified by the European Community Guidelines 2001/110 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The main criteria relating to honey quality are moisture, electrical conductivity, ash content, reducing sugars, sucrose content, free acidity, diastase activity, hydroxymethylfurfural (HMF) content, and microbiological characteristics such as presence of Enterobacteriaceae, yeasts and molds, sulfite-reducing anaerobic and total aerobic bacteria 3 . The most common forms of honey tampering are an addition of cheap sweeteners (such as cane sugar or refined beet sugar, corn syrup, high fructose or maltose syrup) and honeybees fed with sucrose 11 .…”
Section: Introductionmentioning
confidence: 99%